(untitled) (Research, Society and Development, 2022)
The biggest challenge for the food industry is the loss of quality of food products during storage. A potential alternative is the application of coatings that provide moisture barrier properties. Coating of products with solution by spraying techniques (fluidized beds and spouted) has been developed in the pharmaceutical and food industry. Materials such as proteins, carbohydrates and polysaccharides have been widely used due to their biodegradability, biocompatibility, non-toxicity and availability. This article reviews the current state of fluidized and spouted bed technology based on the search strategy to understand the development of these techniques in coating materials (particles, biopolymers, seeds, extracts and oils). This review is intended to provide information on general product coating methods such as fluidized bed spraying and spouting. This review adopted a systematic approach to carefully investigate and analyze literature studies published from initial reports through 2021. After searching Science Direct, Scopus, Web of Science, Capes Peridódicos and FSTA - Food Science and Technology Abstracts studies were evaluated in this study. This review concludes that an approach was carried out that produced interesting results on dry products, coating device, coated products with high biological and technological value. However, a more detailed approach is needed to advance knowledge and accelerate the development of these products to select coating materials and application methods used widely on an industrial and laboratory scale.